World War II - Callery, Sean. (New York : Scholastic Inc., 2024)
This nonfiction guide to World War II has a metal embossed replica tank on the front cover. This book includes compelling photography, illustrations, maps, timelines, and infographics for easy reference. This incredible compilation of facts and photos is expert-reviewed and presents key points and moments from this historic war in a highly engaging package.
The path to war -- Europe & the Atlantic war -- War in the Pacific -- War in Africa & the Middle East - The end of the war.
3-6
The guide to total war - Cover.
Includes index.
Keywords: World War, 1939-1945.; World War, 1939-1945 -- Pictorial works; Informational works